PENGARUH PENGELOLAAN PENGADUAN TERHADAP KEPUASAN PESERTA DI PT. TASPEN (PERSERO) KANTOR CABANG PADANG - Tessa Azhari; Aldri Frinaldi (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2019)
Abstract The purpose of this study was to analyze complaint management for participant / customer satisfaction at PT. Taspen (Persero) Padang Office. This research is quantitative with associative methods. The background of this research is that there werw still complaints management that had not been optimal. This research was conducted at PT. Taspen (Persero) Padang Office with a total population of 131,233 participants, consisting of active civil servants and retired civil servants. The sample in this study consisted of 100 respondents determined by Slovin formula. The data of this study were collected through questionnaires with Likert scale measurements. The data of this study were analyzed by the Simple Regression test. The results of this study proved that there is a complaint management variable on the satisfaction of participants/customers at PT. Taspen (Persero) Padang Office. Keywords: Complaint Management, Participant/ Customer Satisfaction